WANPRESTATIONS IN MUSLIM CLOTHING SALE AND PURCHASE AGREEMENTS ARE LINKED TO AGREEMENT LAW AND TASIKMALAYA STATE COURT RULING NUMBER 28/Pdt.G/2021/PN Tsm - Fahmi Ilyas Fatah (Universitas Labuhanbatu, 2024)
The agreement is a law for the parties who make it. If the agreement is not implemented, then a breach of contract occurs. The author examines defaults in sales and purchase agreements for Muslim clothing with the aim of finding out and analyzing defaults in sales and purchase agreements in terms of contract law. Apart from that, to find out and analyze the decision of the Tasikmalaya District Court regarding default in the sale and purchase agreement for Muslim clothing. This research is descriptive in nature. This type of research is normative legal research. The approach methods used are the regulatory approach and the case approach. Data was obtained through document study and analysis using qualitative normative methods. It’s implementation there was a default by Andri Kristian as the buyer (Defendant), namely only paying the price of Muslim clothing and a loan of IDR. 1,000,000,-, while the remaining purchase and loan price is IDR. 751,760,000,- not paid. Andri Kristian committed a breach of contract in the form of fulfilling his achievements, but not as he should. The Tasikmalaya District Court's decision regarding breach of contract in the sale and purchase agreement for Muslim clothing, among other things, in the main case: granted the Plaintiff's claim in part; stated that the transaction was valid by law in the form of a receipt for the Defendant's goods from the Plaintiff amounting to a total of IDR. 447,000,000,-; stated that it was legal for the Defendant to send the loan money from the Plaintiff amounting to IDR. 305,760,000,-; stated that the receipt for the payment of the Defendant's debt to the Plaintiff was valid by law in the amount of IDR. 1,000,000,-; declare as legally valid the letter signed by the Defendant and Plaintiff on January 13 2020; stated that the Defendant had broken his promise (default) to the Plaintiff; punished the Defendant to pay the remaining debt/remaining obligation to pay the Plaintiff amounting to IDR. 751,760,000,-; reject the Plaintiff's claim for other than that; and sentenced the Defendant to pay court costs of IDR. 1,190,000,-. Keywords: Agreement; Breach of Contract; Buy and Sell; Borrowings